Combating browning: mechanisms and management strategies in in vitro culture of economic woody plants - Chen Liu; Hongrui Fan; Jiaqi Zhang; Jianing Wu; Mingbing Zhou; Fuliang Cao; Guiyun Tao; Xiaohong Zhou (Forestry Research)
Browning presents a significant challenge in the in vitro culture of economically important woody plants, primarily due to high levels of lignification and the accumulation of secondary metabolites. This phenomenon hampers the development of efficient regeneration and genetic transformation systems across diverse species. This review examines the internal and external factors contributing to browning, including genetic attributes, tree genotypes, physiological state of explants, explant surface sterilization, medium composition, and overall culture conditions. It explores the underlying mechanisms of browning, particularly enzymatic browning caused by the oxidation of phenolic compounds, and highlights the crucial role of redox pathways and phenolic metabolism. Conventional methods for assessing browning, such as sensory evaluation by researchers and the examination of paraffin sections stained with toluidine blue, are commonly used but introduce significant delays and potential biases. The review emphasizes the importance of accurate and timely browning assessment methods, notably the use of Fluorescein diacetate (FDA) staining, as a reliable and quantitative measure of cell viability to better evaluate browning intensity and progression. Additionally, this review explores the potential manipulation of key genes in the phenylpropanoid pathway to lower phenolic biosynthesis. Advanced strategies, such as regenerative gene manipulation and natural product encapsulation, are also discussed for their potential to improve regeneration outcomes. By integrating recent advancements in molecular biology and tissue culture techniques, this review offers novel insights and potential solutions for mitigating browning, thereby enhancing the regeneration capacities of woody plants. This comprehensive approach addresses the mechanistic bases of browning and underscores the importance of optimizing cultural practices and genetic strategies to overcome this challenge.